Radiation Embrittlement of Nuclear Reactor Pressure Vessel Steels: An International Review (Third Volume) 1989
DOI: 10.1520/stp10386s
|View full text |Cite
|
Sign up to set email alerts
|

The Swiss Research Program on Irradiation Embrittlement and Annealing of Reactor Pressure Vessel Steels

Abstract: The present research program on irradiation embrittlement and annealing of reactor pressure vessel (RPV) steels in Switzerland is carried out at the Paul Scherrer Institute for Reactor Research. The particular program structure and its relation to the concept for an improved surveillance program is described. Based on past experience with surveillance programs, especially for older plants, the main goal of the research program is determined by an effort to overcome identified shortcomings.Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…The neutron irradiation was performed in the 10 MW SAPHIR reactor [at a neutron flux of $ 4 Â 10 12 cm À2 (fast component >1 MeV)] in Switzerland according to the reactor parameters described in Ref. [18], and at various fluences in the range 0:85-5:0 Â 10 19 cm À2 . The irradiation temperature was controlled at 560 AE 5 K. Thermal annealing (at 735 K for a duration of 168 h) of irradiated samples was conducted in a hot cell under a protective gas atmosphere.…”
Section: Materials and Irradiationmentioning
confidence: 99%
See 1 more Smart Citation
“…The neutron irradiation was performed in the 10 MW SAPHIR reactor [at a neutron flux of $ 4 Â 10 12 cm À2 (fast component >1 MeV)] in Switzerland according to the reactor parameters described in Ref. [18], and at various fluences in the range 0:85-5:0 Â 10 19 cm À2 . The irradiation temperature was controlled at 560 AE 5 K. Thermal annealing (at 735 K for a duration of 168 h) of irradiated samples was conducted in a hot cell under a protective gas atmosphere.…”
Section: Materials and Irradiationmentioning
confidence: 99%
“…The displacement-per-atom (dpa) parameter was calculated in order to characterize the radiation damage level. For the calculations, the neutron flux spectrum [18] has been used as input to the SPECTER computer code [19]. A simplified calculation gave the dpa doses ranging from 1:2 Â 10 À2 to 7:1 Â 10 À2 dpa for 0.85 to 5:0 Â 10 19 cm À2 exposed specimens, respectively, if the threshold energy for Fe displacement is assumed to be 24 eV.…”
Section: Materials and Irradiationmentioning
confidence: 99%
“…This MD contribution added increasingly to hardening at fluxes above 4 × 10 12 n.cm −2 s −1 . Data (Mader, 1995) from steels with <~0.01 wt% Cu confirmed that the appropriate trend occurred when only matrix damage was present, as illustrated in Figure 1.…”
Section: Ucsb and Radamo Campaignsmentioning
confidence: 61%
“…In the 1990s Odette and co-workers exposed A533B-type steels of multiple compositions at high fluxes 5 × 10 11 -6 × 10 13 n.cm −2 s −1 , in the University of Virginia and PLUTO MTRs (the UV-P campaign) (Odette et al, 1993;Mader, 1995). They found that hardening at a given fluence in 0.4 wt% Cu steels decreased with increasing flux while that in 0.11-0.16 wt% Cu steels increased.…”
Section: Ucsb and Radamo Campaignsmentioning
confidence: 99%
“…CRP damage is one of the two contributions to embrittlement better known experimentally. Both transmission electron microscopy (TEM) and techniques such as positron annihilation spectroscopy (PAS), Mössbauer spectroscopy (MS), thermoelectric power (TEP), anomalous small-angle X-ray scattering (ASAXS) [23] and small-angle neutron scattering (SANS) [22] have allowed the experimental characterization of the size of the precipitates, the relative number of these nanostructures, their composition and their volumetric fraction [19][20][21].…”
Section: Introductionmentioning
confidence: 99%